A cold call on work-based learning: a "live" group project for the strategic selling classroom. Issue 3 (12th August 2019) - Lloyd, Robert; Martin, Michael J.; Hyatt, James; Tritt, Addison
Abstract : Purpose: The purpose of this paper is to describe a case study used in a strategic sales class that employs the use of work-based learning pedagogy to expose students to real-life cold calling experiences. This real-life cold calling experience involves students within the course building a target list of prospective students for a small liberal arts college. The students must then construct pre-call strategies, build rapport with prospective students and finally "close the deal" by having the prospective student visit campus. Design/methodology/approach: This paper begins by describing work-based learning as a unique pedagogical method and the importance of cold-calling skills in the context of workplace skills in demand. Theoretical foundations in Lichtenstein and Lyon's (1996) entrepreneurial skillset is analyzed, as is the application of "live" group projects. The case is then described in detail and focuses on the project itself, the personal and group incentives used in the course of the project, and finally, a review of the learning outcomes and desired skillset outcomes for the class. Findings: The case shows that students can learn and implement the behaviors, attitudes and practices that make professional cold-callers successful. The impact on the university can also be seen since real contributions were made to the recruiting efforts of the college vis-à-vis higher matriculation numbers. The entrepreneurial skillsets and "live" group project literature is contextualized in light of the findings of the project. This research found that students engaged in varying levels of progress in their managerial, entrepreneurial, technical skillsets as well as levels of personal maturity. Finally, the authors provide guidance for future research to expound the findings of this project by testing the variables using quantitative methodologies. Originality/value: The paper showcases an innovative pedagogic approach to exposing students to the best practices of cold-calling and allows them to exercise these tools real time as they make actual cold calls and work toward sales incentives. The focus on recruiting new students as customers of the college serves is not only active classroom learning, but it also serves mission-based outcomes to help the college achieve desired recruiting goals. This case study will provide a tool for small, liberal arts colleges to use which mobilizes faculty and students in the effort to recruit new students, in an environment where enrollment numbers are falling for this market sector in higher education.